Prediction method for ground shock parameters of explosion in concrete. (12th July 2021) - Mu, Chaomin; Zhou, Hui; Ma, Haifeng
Highlights: Adopt free-field tests and dimensional analysis, and verify the results by LS-DYNA. Prediction formulas for ground shock parameters of explosions at different SDOB. When SDOB reaches 1.2 m/kg 1/3, the explosion energy is completely enclosed. Attenuation gradient of ground shock is related to the concrete strength grade. Introduce DOB coefficient of equivalent energy instead of using coupling coefficient. Abstract: The ground shock caused by the explosion is the main load causing the destruction of underground engineering. To study the propagation law of ground shock parameters in concrete, free-field tests of explosions at seven different scaled depth of burial (SDOB) have been carried out by using self-constructed concrete blocks with large-sizes. The results indicate that when the SDOB ranges from −0.25 to 1.2 m/kg 1/3, the pressure and acceleration at the same scaled distance from the explosion center increase with the SDOB. When the SDOB reaches 1.2 m/kg 1/3, the explosion energy is completely enclosed into underground, and the coupling coefficient reaches 1.0. Combined with the dimensional analysis theory, it is found that when the SDOB of an explosion is determined, the propagation law of pressure and acceleration presents a power function attenuation with the increase of the scaled distance from the explosion center. For the three different strength grades of C30, C50, C70 concrete under semi-buried explosion, the attenuation gradient of the pressure or acceleration is inconsistent with an increase in the scaled distance from the explosion center. The higher the concrete strength, the slower the gradient changes. By introducing the depth of burial (DOB) coefficient of equivalent energy, the prediction method of ground shock parameters at different SDOB of explosion and explosions with different mass of charge can be obtained, and it has high accuracy for calculating the ground shock parameters of explosion with large mass charge which verified by numerical simulation.